Studi dan Strategi Pengembangan Produk Ekowisata Bunder (Bangsring Underwater) di Desa Bangsring Kecamatan Wongsorejo Kabupaten Banyuwangi - Nur Aini; Hasan Zayadi; Saimul Laili (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2018)
Management can be done by creating the ecotourism model with making products or tourism attraction in an integrated manner become alternative strategy which is environmentally friendly. The goal of this research is to know the tourism product and the strategy to develop the ecotourism based on advanced conservation in the BUNDER (Bangsring Underwater) at Wongsorejo Banyuwangi Regency. The method of this research is descriptive qualitative, fields observation, based on the the information relate to the ecotourism product and management, determination of respondents use purposive sampling both interview and questionnaire. The respondents consist of tourist management and the local government. Analysing the data use SWOT analysis. The result of the analysis shows that the ecotourism product of BUNDER (Bangsring Underwater): snorkelling, diving, floating home, shark clinic, fish apartment, marine education, banana boat, jet ski, Cano/paddle, and reading park. The SWOT analysis based on the respondents from (developer, government, and tourists) produce some strategies which are recommended. There are steps of strategies to develop the ecotourism product to support the resource utilization as advanced ecotourism area those are : enhance the promotion and publication intensively, adding facilities and infrastructure, warn the tourist not to destroy the nature, increasing the ecotourism potential management to be interesting ecotourism product, division of tasks to employees in every ecotourism product, conducting the training programs to the increasing the human resources of fisherman and the effort to the processing waste to be more productive. Keywords: Ecotourism products, analysis SWOT, Conservation strategy ABSTRAK Pengelolaan menggunakan model ekowisata berupa produk atau atraksi ekowisata secara terpadu menjadi alternatif strategi yang ramah lingkungan. Tujuan penelitian adalah untuk mengetahui produk ekowisata dan strategi untuk pengembangan ekowisata berbasis konservasi berkelanjutan di BUNDER (Bangsring Underwater) Wongsorejo Kabupaten Banyuwangi. Metode penelitian deskriptif kualitatif, observasi lapangan, berdasarkan informasi mengenai produk ekowisata dan pengelolaan,penentuan responden menggunakan purposive sampling dengan teknik wawancara dan kuesioner, responden meliputi, pengelola, wisatawan dan pemerintah setempat. Datadianalisis menggunakan analisis SWOT. Hasil penelitian menunjukkan bahwa Produk ekowisata BUNDER: snorkeling, diving, rumah apung, klinik hiu, fish apartement, marine education, banana boat, jet ski, kano/padle, dan taman baca. Analisis SWOT berdasarkan respon dari (pengelola, pemerintah dan wisatawan) menghasilkan beberapa strategi yang dapat direkomendasikan. Adapun langkah-langkah strategi pengembangan produk ekowisata yang dilakukan untuk menunjang pemanfaatan sumberdaya sebagai area ekowisata berkelanjutan yaitu: Peningkatan promosi dan publikasi secara intensif, menambah fasilitas sarana maupun prasarana ekowisata, Menghimbau wisatawan supaya tidak merusak alam, Peningkatan pengelolaan potensi ekowisata menjadi produk ekowisata yang menarik, pembagian tugas pada karyawan disetiap produk ekowisata, mengadakan pelatihan-pelatihan kepada SDM nelayan dan upaya mengolah sampah dengan lebih produktif. Kata kunci: Produk ekowisata, Analisis SWOT, Strategi konservasi